2015
DOI: 10.1109/tpami.2014.2362759
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Estimation from Face Images: Human vs. Machine Performance

Abstract: Demographic estimation entails automatic estimation of age, gender and race of a person from his face image, which has many potential applications ranging from forensics to social media. Automatic demographic estimation, particularly age estimation, remains a challenging problem because persons belonging to the same demographic group can be vastly different in their facial appearances due to intrinsic and extrinsic factors. In this paper, we present a generic framework for automatic demographic (age, gender an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(175 citation statements)
references
References 58 publications
10
159
1
1
Order By: Relevance
“…It has also been shown that traits like gender [29,4,12], height and colour [8] and demographics like age and race [13] can be automatically estimated successfully from body images. In summary, the question is not if, but how such semantic information can be discerned and utilised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that traits like gender [29,4,12], height and colour [8] and demographics like age and race [13] can be automatically estimated successfully from body images. In summary, the question is not if, but how such semantic information can be discerned and utilised.…”
Section: Discussionmentioning
confidence: 99%
“…It also connects to global pools of contributors, therefore unambiguous and decisive questions must be presented. We would ideally like to improve upon the crowdsourcing work of [13], who spent a significant sum of money collecting a large number of human intelligence tasks (HITs), only to gain few valid responses. Additionally, the goal is to collect geographically unconstrained data to better model average human perception and description of others, compared to more isolated annotation tasks like [36].…”
Section: Crowdsourcing Taskmentioning
confidence: 99%
“…The problem of demographic estimation has been studied extensively in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23]. Existing demographic estimation approaches can be grouped into three main categories: landmarks-based approaches, texture-based approaches, and appearance-based approaches.…”
Section: Demographic Estimationmentioning
confidence: 99%
“…However, manual annotation in facial landmark detection limits the usability of such approaches in automatic demographic estimation systems. Texture-based approaches, such as [16,17,20], utilize facial texture features, e.g., local binary patterns (LBP), Gabor, and biologically inspired features (BIF). Although used in many demographic estimation approaches, high feature dimensionality makes such approaches less efficient.…”
Section: Demographic Estimationmentioning
confidence: 99%
“…There have been many works on classifying attributes directly from images, for facial verification [12], demography from face [10], gender estimation from face and body [18], describing faces and scenes [20], describing clothing [11] and describing texture [17]. A large portion of related research is also dedicated to recognising attributes from pedestrians and surveillance footage [29,1,21,13].…”
Section: Related Workmentioning
confidence: 99%